ANALISIS FAKTOR-FAKTOR PENERAPAN PENGADAAN BARANG/JASA PEMERINTAH SECARA E-PROCUREMENT TERHADAP PENYERAPAN ANGGARAN DI KOTA SABANG - Sawidar Sawidar; Muttaqin Muttaqin; Anita Rauzana (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Regulation of the President of the Republic of Indonesia Number 54 Year 2010 on Procurement of Government Goods/Services, has come to the fourth change, with the issuance of Presidential Regulation No. 4 of 2015. Sabang City Government has implemented this Presidential Regulation in fiscal year 2015 until now. If the procurement of goods/services runs well, it will increase the absorption of the budget. The purpose of this study is to identify the dominant variables applied in the procurement of electronic goods/services (e-procurement), as well as to analyze the relationship and influence of procurement factors of goods/services of government on e-procurement towards budget absorption in Procurement Unit ULP) Sabang City. The number of population in this study was 88 respondents. The results showed that the dominant variable applied in the procurement of goods/services of government by e-procurement is the access factor of information with the mean of 4.702. The quality factor of the system and accountability has a very weak relationship with Pearson coefficient of 0.001 and 0.191, transparency factor, market access and business competition, and procurement efficiency has a weak relationship with Pearson coefficient of 0.322, 0.226 and 0.201, while monitoring and auditing factors, and access to information has a moderate relationship with Pearson coefficient of 0.479 and 0.524 against budget absorption. The influence of government procurement/procurement factors on the budget absorption, which influences is the factor of transparency, accountability, and access factor of information with tcount greater than ttable and significance value lower than 0.05.